(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In the context of the sharp intensification of global competition and the development of a knowledge-based economy, the quality of education has become a decisive factor for a country’s long-term economic stability and competitiveness. International assessment programs—PISA, PIRLS, and TIMSS—serve as important tools for objectively evaluating the effectiveness of education systems and for shaping strategies aimed at developing a nation’s human capital. This article analyzes the essence of these programs, their impact on the national economy, and the ways in which they provide guidance for the implementation of educational reforms.